2021
DOI: 10.1007/s11274-021-03052-z
|View full text |Cite
|
Sign up to set email alerts
|

Industrial sustainability of microbial keratinases: production and potential applications

Abstract: Keratinases are proteolytic enzymes with a particular ability to cleave peptide bonds in keratin, and in other proteins. Due to their broad-spectrum of activity, keratinases are considered viable substitutes for chemical and thermal treatments of proteinrich industrial by-products. Among these protein residues, special attention has been given to keratinous materials (feathers, hair, horns, etc.), which disposal through harsh conditions methods, such as acid/alkaline hydrolysis or incineration, is not consider… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(20 citation statements)
references
References 95 publications
(103 reference statements)
0
14
0
2
Order By: Relevance
“…Since the cost of keratinase production is high, several researchers have increased the yield and stability of keratinases by altering the genome of keratinolytic organisms via physical and chemical mutagenesis or recombinant DNA technologies [ 80 , 82 , 90 , 93 , 94 , 95 , 96 ]. Keratinases have become increasingly popular, and many studies have reviewed their discovery, production, classification, structure, hydrolysis function, and industrial application [ 9 , 97 , 98 , 99 , 100 ]. Biological techniques are environmentally friendly methods to hydrolyze keratin, but they require more time than other methods.…”
Section: Methods For the Valorization Of Livestock Keratinmentioning
confidence: 99%
“…Since the cost of keratinase production is high, several researchers have increased the yield and stability of keratinases by altering the genome of keratinolytic organisms via physical and chemical mutagenesis or recombinant DNA technologies [ 80 , 82 , 90 , 93 , 94 , 95 , 96 ]. Keratinases have become increasingly popular, and many studies have reviewed their discovery, production, classification, structure, hydrolysis function, and industrial application [ 9 , 97 , 98 , 99 , 100 ]. Biological techniques are environmentally friendly methods to hydrolyze keratin, but they require more time than other methods.…”
Section: Methods For the Valorization Of Livestock Keratinmentioning
confidence: 99%
“…Indeed, bacteria, actinomycetes, and fungi are shown to have the capability to degrade keratin (Calin et al, 2017 ; Bohacz and Korniłłowicz-Kowalska, 2019 ). Many researchers have isolated keratin-degrading microorganisms from different environments and proved that these microorganisms can be utilized to convert keratinous wastes into value-added products (de Menezes et al, 2021 ; Nnolim and Nwodo, 2021 ). These isolated microorganisms exhibited their potential to degrade keratin and keratin-containing wastes such as feathers into soluble fractions and amino acids (Callegaro et al, 2018 ; Shanmugasundaram et al, 2018 ; Bohacz, 2019 ; Tamreihao et al, 2019 ; Chaudhary et al, 2021 ).…”
Section: Microbial Degradation Of Keratinmentioning
confidence: 99%
“…Interestingly, a study showed that glucose and ammonium nitrate are not good sources for growing Stenotrophomonas maltophilia to degrade feathers ( Qu et al, 2018 ). Accumulated studies suggest that different microorganisms require various fermentation conditions for large-scale production, indicating that careful exploratory studies are necessary prior to the large-scale production of the enzymes ( Jagadeesan et al, 2020 ; de Menezes et al, 2021 ; Deniz et al, 2021 ; Sharma and Kango, 2021 ). It was demonstrated that the solid-state fermentation increased keratinase production compared with the commonly used submerged fermentation ( Inácio et al, 2018 ).…”
Section: Mechanism Of Action For Keratinasementioning
confidence: 99%
“…As keratin does not accumulate in nature, microorganisms are playing the major role in its degradation and recycling. Therefore, keratinous wastes threatening the environment can be converted into value-added products by using microbial treatment ( de Menezes et al, 2021 ; Nnolim and Nwodo, 2021 ). Extensive studies have been carried out to search suitable microorganisms and obtain optimized processes to make full use of keratinous wastes ( Gradišar et al, 2000 ; Sangali and Brandelli, 2000 ; Kim et al, 2001 ; Rai and Mukherjee, 2011 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation